Challenges in Communicating Climate Change to Extension Audiences - Martha C. Monroe; Claire Layman Bode; Mark A. Megalos (EDIS)
Media coverage of climate change can often leave the average person confused and unsure what to believe. However, as a trusted source of information and research, Extension has the opportunity to educate people about climate change and appropriate adaptation strategies in a scientific, unbiased way. This 5-page fact sheet outlines four challenges of climate change education. Written by Martha Monroe, Claire Layman Bode, and Mark A. Megalos, and published by the UF School of Forest Resources and Conservation, May 2015.